Restraint : a new foundation for U.S. grand strategy - Posen, Barry (Cornell studies in security affairs., 2014)
"The United States, Barry R. Posen argues in Restraint, has grown incapable of moderating its ambitions in international politics. Since the collapse of Soviet power, it has pursued a grand strategy that he calls 'liberal hegemony, ' one that Posen sees as unnecessary, counterproductive, costly, and wasteful. Written for policymakers and observers alike, Restraint explains precisely why this grand strategy works poorly and then provides [an] ... alternative grand strategy and an associated military strategy and force structure"--Dust jacket flap